2020
DOI: 10.1007/s11409-020-09228-6
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive awareness as measured by second-order judgements among university and secondary school students

Abstract: When compared to high performers, low performers generally have more difficulty to accurately estimate their own performance. This has been explained by low performers being both unskilled and unaware about their performance. However, Miller and Geraci Journal of Experimental Psychology: Learning, Memory, and Cognition, 37(2), 502-506, (2011) found that low performing university students also assigned less confidence to their estimates (i.e., second-order judgments, SOJs), indicating some metacognitive awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…This means that the problem-based learning model assisted by blended learning has a significant impact on students' metacognitive awareness compared to the problem-based learning model. These results are in line with research by Roebers [18] and Nederhand et al [19] which is caused by learning by using the internet which is often called e-learning or blended learning.…”
Section: Resultssupporting
confidence: 91%
“…This means that the problem-based learning model assisted by blended learning has a significant impact on students' metacognitive awareness compared to the problem-based learning model. These results are in line with research by Roebers [18] and Nederhand et al [19] which is caused by learning by using the internet which is often called e-learning or blended learning.…”
Section: Resultssupporting
confidence: 91%
“…Low performers may be more likely to use surfacebased cues, such as answer fluency, which are not reliable. This conclusion is consistent with previous research showing differences in cue utilization among students at different levels of performance (Thiede et al, 2010;Ackerman and Leiser, 2014;Gutierrez de Blume et al, 2017). For instance, Ackerman and Leiser (2014) reported that low achievers -when regulating their learning of text-were more sensitive to unreliable, surface-level cues than high achievers.…”
Section: Discussionsupporting
confidence: 91%
“…Calibration strategies help align learners' perceived engagement in behavior with their actual engagement in it, reducing overconfidence and misjudgment by helping them understand they are often doing something more or less than originally thought. Numerous studies have illustrated that learners are generally overconfident about their skills and knowledge (De Bruin et al, 2017;Kruger & Dunning, 1999;Sanchez & Dunning, 2018), particularly when lacking mastery (Miller & Geraci, 2011;Nederhand et al, 2021). In other words, learners often err more than they think they are or apply their learning less than they suspect.…”
Section: Attitudinal Change Strategiesmentioning
confidence: 99%
“…In their classic review of attitudinal change strategies for education, Bednar and Levie (1993) found that along with providing a persuasive message and modeling and reinforcing target behaviors, inducing dissonance between attitudinal components is a common approach to changing learners’ attitudes. Some attitudinal change models have now expressly directed educators to create and identify dissonance in associated components (see Mueller et al, 2017). This emphasis on dissonance stems from cognitive dissonance theory, which suggests that when people's beliefs and actions are incongruent, they experience dissonance or discomfort.…”
Section: Introductionmentioning
confidence: 99%